(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
During the regime of Porfirio Diaz, the army was well known for being used as a repressive resource of the government. However, several inves tigations show the opposite conclusions, even though sometimes indeed, the army was used to quell riots of some importance, most of the times it was reserved for other tasks. In addition its preparation, moral and disci- pline was very much affected due to the policy of “leeway” of the regime, as well as customs inherited from as far back as the colonial and indepen- dence. However, some efforts were made concerning improving educa- tion of the army. However, the reality was that these efforts gave very few and poor results, as priority was given to upper-class soldiers from the institution and the rest were relegated, with the consequent result: lower class soldiers were known by their ignorance and discontent, base of any armed force. So, this little work is to show the conditions of edu- cation in one of the most important institution in the country: the army.